Dual discrepancy/consistency pattern of strengths and weaknesses method of specific learning disability identification: Classification accuracy when combining clinical judgment with assessment data. (June 2022) - Maki, Kathrin E.; Kranzler, John H.; Moody, Mary Elizabeth
Abstract: The Dual Discrepancy/Consistency (DD/C) pattern of strengths and weaknesses (PSW) method is the most prominent "other alternative research-based procedure" used to identify a specific learning disability (SLD). The DD/C method is intended to be used with multiple data sources, but no research has examined identification decision making using the DD/C PSW analysis of cognitive and academic achievement test scores with other assessment data (e.g., pre-referral intervention data, parent/teacher reports, observations, evaluation of exclusionary factors). This study used an experimental vignette methodology to investigate school psychologists' ( N = 343) identification decision making using the DD/C method with multiple data sources. Results showed that school psychologist participants made highly accurate (97.50%) identification decisions when both cognitive and achievement test score patterns and other assessment data were clearly indicative of SLD, but that overall identification accuracy was only 65.60%. Participants made less accurate identification decisions when examining test score data that did not meet DD/C PSW criteria for SLD than when examining test score data that did. Participants made less accurate decisions when other assessment data (interpreted in conjunction with test scores) did not meet DD/C PSW criteria for SLD or were ambiguous than when they did. In addition, male school psychologists were less likely to make accurate identification decisions than female school psychologists, and participants who were Nationally Certified School Psychologists were less likely to make accurate identification decisions than those who were not. Last, more experience with DD/C resulted in less accurate identification decisions, and participants who made accurate decisions reported higher levels of confidence, although the effect size was negligible. Implications for research and practice are discussed.